Composites forming technologies - Long, A. C. (Andrew Craig) (Woodhead publishing in textiles ;, 2007)
Composites are versatile engineered materials composed of two or more constituent materials which, when combined, lead to improved properties over the individual components whilst remaining separate on a macroscopic level. Due to their versatility, composite materials are used in a variety of areas ranging from healthcare and civil engineering to spacecraft technology. Composites forming technologies reviews the wealth of research in forming high-quality composite materials. The book begins with a concise explanation of the forming mechanisms and characterisation for composites, as well as covering modelling and analysis of forming techniques. Further chapters discuss the testing and simulation of composite materials forming. The book also considers forming technologies for various composite material forms including thermoset and thermoplastic prepreg, moulding compounds and composite/metal laminates. With its distinguished editor and array of international contributors, Composites forming technologies is an essential reference for engineers, researchers and academics involved with the production and use of composite materials. Reviews the wealth of research in forming high-quality composite materialsIncludes a concise explanation of the forming mechanisms and characterisation for compositesConsiders forming technologies for various composite material forms.